The Antagonistic Correspondence of 1801 between Chaplain Sack and his Protégé Schleiermacher - Blackwell, Albert L. (Harvard theological review, 1981)
In the summer of 1801 a sharp, even bitter exchange of correspondence passed between the Court and Cathedral Preacher in Berlin, Friedrich Samuel Gottfried Sack, and his ministerial protégé Friedrich Schleiermacher. The points of contention were Schleiermacher's circle of Berlin friends, whom Sack considered inappropriate company for the young minister, and Schleiermacher's book of 1799, On Religion: Speeches to Its Cultured Despisers, containing theological views judged by Sack to be irreconcilable with the Christian religion Schleiermacher had been ordained to preach. This candid exchange was Schleiermacher's first official encounter with rising tensions between his theological liberalism and the orthodoxy of his Reformed Church background. Indeed these two letters argue theological issues that plagued Schleiermacher throughout his career and have haunted his theology to our own day, the most central of these being Schleiermacher's refusal to apply terms of personality to God. Yet these seminal letters have received scant attention in German secondary literature, and to the English reader they have remained all but inaccessible.